Workforce Analysis of Female Pelvic Medicine and Reconstructive Surgery, 2015 to 2045. Issue 5 (September 2016) - Brueseke, Taylor; Muffly, Tyler; Rayburn, William; Connolly, AnnaMarie; Nieto, Maria; De La Cruz, Jacquia; Wu, Jennifer
Abstract : Objectives: The aim of this study was to assess how the projected increase in prevalence of pelvic floor disorders (PFDs) will impact the number of patients per female pelvic medicine and reconstructive surgery (FPMRS) subspecialist between 2015 and 2045. Methods: We performed a workforce analysis of FPMRS subspecialists in the United States by developing a model to predict the number of FPMRS subspecialists in 5-year increments from 2015 to 2045. Our model allowed for selection of the number of current FPMRS subspecialists, the number and sex of new FPMRS subspecialists added per year, and retirement age of FPMRS subspecialists. The number of women with PFDs from 2015 to 2045 was then predicted by applying published, age-specific prevalence rates to the 2012 US Census Projections for women aged 20 years or older. For our primary outcome, we divided the projected number of patients by the projected number of FPMRS subspecialists every 5 years from 2015 to 2045. Results: The model predicts the number of FPMRS subspecialists will increase from 1133 to 1514 with a sex shift from 46% female to 81% female between 2015 and 2045. The number of women with ≥1 PFD is predicted to increase from 31.4 million in 2015 to 41.9 million in 2045. For our primary outcome, the number of patients per FPMRS subspecialist is projected to range from 27, 870 in 2015 to 27, 650 in 2045. Conclusions: The current ratio of patients per FPMRS subspecialist appears high and is predicted to remain near current levels over the next 30 years. These projections support the need for continued training of physicians skilled in treating PFDs. Abstract : Continued training of Female Pelvic Medicine and Reconstructive Surgery subspecialists will be necessary to maintain the current ratio of patients to provider as the prevalence in pelvic floor disorders increases over the next 30 years.